A Adat, dan Harmoni: Studi Kasus Peran Kearifan Lokal “Lubuk Larangan” bagi Kelestarian Biodiversitas Ekosistem Sungai Masyarakat Mandailing Natal - Rizki Khairani Nasution (INSTITUT AGAMA ISLAM NEGERI AMBON, 2026)
This study aims to examine the role of the local wisdom known as Lubuk Larangan in preserving the biodiversity of river ecosystems in Mandailing Natal, North Sumatra. Lubuk Larangan is a traditional practice that prohibits the catching of fish and other aquatic life in specific river areas for a period determined by the indigenous community. This tradition serves not only as a form of natural resource management based on local wisdom but also reflects the values of togetherness, sustainability, and respect for nature that have been passed down through generations. The research methodology uses a qualitative approach with data collection techniques that include in-depth interviews with customary leaders, community figures, and local fishermen, as well as participatory observation at the Lubuk Larangan sites. The data obtained are analyzed descriptively to understand how the system of values, norms, and customary sanctions is applied in this conservation mechanism. The results of the study show that the Lubuk Larangan tradition is proven effective in maintaining the sustainability of river ecosystems. This tradition not only limits the exploitation of aquatic resources through clear customary rules but also serves as an environmental education medium for the younger generation, strengthens social bonds within the community, and maintains ecological balance. The active participation of the community, adherence to customary norms, and the enforcement of strict social sanctions are the main factors supporting the success of this practice. Thus, this research confirms that Lubuk Larangan is not just a local cultural heritage but also a traditional conservation mechanism that is relevant to the concept of sustainable development. The integration of this local wisdom with modern natural resource management policies can be an effective model for preserving biodiversity and the harmony between humans and nature. Keywords: Tradition, Lubuk Larangan, Local Wisdom, Conservation, Biodiversity, Mandailing Natal